KUALITAS AIR DAN HUBUNGANNYA DENGAN KEBERADAAN PLANKTON DI SUNGAI SUNGGAL PROVINSI SUMATERA UTARA (Water Quality and the Connection in Plankton Existence in Sunggal River of Nort Sumatra) - Meisara Karolina; Miswar Budi Mulya; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Water quality show grade or water conditions that associated with activities or certain purposes. The changes of water quality has influence to species exixtence and amount of water biota like plankton. This research was conducted from April to May 2014 to see the Sunggal River quality in related to PP No. 82 Tahun 2001 using STORET Method and to know the plankton diversity. The samples were taken from three observation stations with 3 replications. The sampling point was determined using Purposive Random Sampling method. From the result with STORET method, Sunggal River at station I was experienced with the heavy pollution with score of -10 and at station II and III was experienced with the medium pollution with score of -18 for allocation of class I. There are ten classes of phytoplankton were found, they are Bacillariophyceae, Chlorophyceae, Chrysophyceae, Cryptophyceae, Conjugatophyceae, Coscinodiscophyceae, Cyanophyceae, Euglenophyceae, Ulvophyceae and Xanthophyceae and 3 classes of zooplankton they are Branchiopoda, Gastropoda and Maxillopoda. The highest value of plankton abudance was at station III as 54 Ind/l and the lowest value of plankton abudance found in station I as 24,8 Ind/l. The highest diversity index (H’) founded at station III is 2,65 and the lowest at station I is 2,32.Keywords : Water Quality, Plankton, Diversity, Sunggal River.